Floating tablets incorporating curcumin solid dispersion as a potential pharmaceutical dosage form for stomach cancer treatment - Duyen Thi My Huynh†, Viet-Hung Tran†, Minh-Ngoc T. Le, Van-Hoa Huynh, Duy Toan Pham (Journal of Applied Pharmaceutical Science, 2023)
Curcumin, a well-known compound commonly used for stomach cancer treatment, possesses inadequate oral bioavailability due to its low water solubility and instability in the digestive-tract alkaline pH. To overcome these issues, this study formulated the curcumin solid dispersion (CSD) (to enhance curcumin solubility) and incorporated this solid dispersion in the floating tablet formula (to bypass the alkaline pH in the intestine). The tablets were optimized by varying numerous parameters including (1) the granulating solvent, (2) the binder excipient, (3) the type of gas-generating excipients, (4) the ratio of gas-generating excipients, (5) the type/amount of matrix generator, and (6) the tablet hardness. The product was then fully characterized in terms of floating potential, floating time, tablet integrity, curcumin solubility/dissolution profiles, long-term and accelerated stability study, in-vitro cytotoxicity, and other physicochemical properties. The best formula possesses a short floating potential of 35 ± 1 seconds, a long floating retention time of >8 hours, good tablet integrity during the floating duration, enhanced curcumin solubility/ dissolution profiles to >200 times, and perfect physicochemical stability for at least 2 years in the normal storage condition. Furthermore, the tablets reserve the curcumin cytotoxicity on the N87 stomach cell lines, with a better efficacy compared to the standard drug 5-FU. Finally, the tablets significantly potentiate and enhance the anticancer effect of 5-FU in a synergistic mechanism. Conclusively, the floating tablet incorporating the CSD could be a potential pharmaceutical product for stomach cancer treatment.
Keywords: Floating tablet, curcumin, solid dispersion, stability, stomach cancer